Refractory and volatile species in the UV-to-IR transmission spectrum of ultra-hot jupiter WASP-178b with HST and JWST - Lothringer, Joshua D.; Bennett, Katherine A.; Sing, David K.; Kehoe-Seamons, Brian; Rustamkulov, Zafar; Reggiani, Henrique; Schlaufman, Kevin C.; McCreery, Patrick; Norris, Seti; Hauschildt, Peter H.; Cacho-Negrete, Ceiligh; Gressier, Amélie; et al. (The astronomical journal, 2025)
The atmospheres of ultra-hot Jupiters are unique compared to other planets because of the presence of both refractory and volatile gaseous species, enabling a new lens to constrain a planet’s composition, chemistry, and formation. WASP-178b is one such ultra-hot Jupiter that was recently found to exhibit enormous near-UV absorption between 0.2 and 0.4 μm from some combination of Fe+, Mg, and SiO. Here, we present new IR observations of WASP-178b with the Hubble Space Telescope (HST) WFC3 and JWST NIRSpec G395H, providing novel measurements of the volatile species H2O and CO in WASP-178b’s atmosphere. Atmospheric retrievals find a range of compositional interpretations depending on which data set is retrieved, the type of chemistry assumed, and the temperature structure parameterization used due to the combined effects of thermal dissociation, the lack of volatile spectral features besides H2O and CO, and the relative weakness of H2O and CO themselves. Taken together with a new state-of-the-art characterization of the host star, our retrieval analyses suggests a solar to supersolar [O/H] and [Si/H], but subsolar [C/H], perhaps suggesting rock-laden atmospheric enrichment near the H2O ice line. To obtain meaningful abundance constraints for this planet, it was essential to combine the JWST IR data with short-wavelength HST observations, highlighting the ongoing synergy between the two facilities.
Online veröffentlicht: 24. April 2025
Gesehen am 17.12.2025